Bridging soil biogeochemistry and microbial communities (archaea and bacteria) in tropical seagrass meadows - Nóbrega, Gabriel Nuto; de Andrade, Pedro Avelino Maia; Queiroz, Hermano Melo; Pereira, Arthur Prudêncio de Araújo; Copertino, Margareth da Silva; Gorman, Daniel; Zhuang, Wen; Song, Jinming; Andreote, Fernando Dini; Otero, Xosé Luis; Ferreira, Tiago Osório (Frontiers in Marine Science, 2023)
Introduction Seagrass meadows are among the most valuable ecosystems, providing numerous ecosystem services and functions. Despite its importance, there is a lack of knowledge about soil’s biogeochemical process variability, which can control microbiological communities. Thus, this study aimed to evaluate whether seagrass meadows in different geo-environments exhibit varying Fe and sulfate reduction intensities, shaping distinct archaea and bacteria communities. Methods Soil samples were collected in seagrass meadows under contrasting climatic, geological, vegetational and hydrological settings along the Brazilian coast (e.g., Semiarid Coast - SC, Southeastern Granitic Coast – GC, and Southern Quaternary Coast - QC). The soils were characterized by particle size, pH, redox potential (Eh), total organic C and total N content, acid-volatile sulfides (AVS), and simultaneously extracted Fe. Furthermore, a solid-phase Fe fractionation was performed to characterize the decomposition pathways in these soils, and the shifts in the microbial community along this spatial variation were analyzed using denaturing gradient gel electrophoresis. Results The studied soils presented a sandy texture (values ranging from 74 ± 11.8 to 80.5 ± 6.4%) caused by energetic hydrodynamic conditions. The pH values were circumneutral, while redox conditions presented significant distinction among the studied sites, ranging from anoxic to oxic (values ranging from -63 to +334 mV). The degree of pyritization (DOP) ranged from< 10% to values higher than 80%, highly influenced by rhizospheric oxidation, and higher AVS content was recorded for sites with lower DOP (i.e., GC and QC). Discussions Thus, biogeochemical processes in the seagrass soils present a wide variation in response to the geo-environmental settings. Plants influence the soil’s geochemical and microbiological communities, retaining fine particles, promoting rhizosphere oxidation, and inducing anoxic conditions controlling the Fe and S forms. Moreover, the same plant species can result in distinct soil conditions and microbial communities due to geoenvironmental settings.